2002
DOI: 10.1542/peds.109.5.e75
|View full text |Cite
|
Sign up to set email alerts
|

Caloric Intake and Eating Behavior in Infants and Toddlers With Cystic Fibrosis

Abstract: , and observations that their child has a poor appetite (32%) and would rather drink than eat (32%). Parents of children with CF chose a greater number of mealtime strategies and feelings as problems and reported more frequently using problematic strategies at mealtimes than did parents of controls. Examples of problematic strategies and feelings for parents of infants and toddlers with CF included feeling anxious/frustrated when feeding their children (37%), not feeling confident that their child eats enough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
98
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 20 publications
12
98
0
2
Order By: Relevance
“…Prior studies have indicated that parent-child behaviors during a meal are similar across three different tapings. [39][40][41] As such, only one taping was performed for each family.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have indicated that parent-child behaviors during a meal are similar across three different tapings. [39][40][41] As such, only one taping was performed for each family.…”
Section: Methodsmentioning
confidence: 99%
“…cognitive-behavioral techniques to managing procedural distress [22] and feeding behavior problems [23,24]. In addition the center psychologist should address psychological factors associated with chronic pain and the effects of segregation, provide a consultation and supervision service to other CF team members, and undertake dissemination of the psychological effects of living with CF within the team.…”
Section: Desirable Responsibilitiesmentioning
confidence: 99%
“…However, children's actual dietary intakes are consistently reported as falling short of these recommendations (Stark, Mulvihill, Jelalian, Bowen, Powers, Tao et al 1997;Powers, Patton, Byars, Mitchell, Jelalian, Mulvihill et al 2002). The practice of self management has been advocated as an approach to helping children with CF increase their calorie intakes (Luder et al 1989) by educating them and their parents to actively partake in self monitoring, decision making and in communicating with professionals (Bartholomew et al, 1991).…”
Section: Introductionmentioning
confidence: 99%